GREGORY PALAMAS ARCHBİSHOP OF THESSALONIKI AND HESYCHASM IN ORTHODOX CHRISTIAN TRADITION - Salih İnci (Trakya Üniversitesi Sosyal Bilimler Dergisi, 2019)
In this study, we will examine the mystical movement as known "Palamism" or "Hesychasm" which was appeared undertaken by Gregory Palamas (1296– 1359) a monk of Athos in the fourteenth century. So we can have more information about the functions of monasteries and their theological and political aspects the in Byzantium world.According to this idea that emerged in the late Byzantine period, Palamas suggested that the recitation of the Jesus Prayer should be accompanied by a psychosomatic technique with the breath, into the heart. But Scholar Barlaam (1290 - 1348) Calabrian objected to this technique by the Thomas Aquino's ideas. Because he claimed that real knowledge about God could only be reached by reason. Eventually both movements that started at theological level, were supported or opposed later by the politics and church circles. This debate, which coincided with the struggle between the dynasties of "Kantekuzenos" and "Paleologos" in Byzantium, is an interesting example of how monastic monks show their effectiveness in theological and political debates when they are organized.